La consulta previa libre e informada, diagnóstico al desafío constitucional ecuatoriano - Gómez Márquez, Miriam Lourdes (2023)
Prior, Free and Informed Consultation is a constitutional principle that directs the State and extractive companies, prior to starting a process of extracting renewable or non- renewable resources, to participate in this initiative to those indigenous peoples and nationalities settled and recognized in Ecuador. This research is aimed at defining and detecting a diagnosis of this principle, regarding its effective application in our territory, and if its proper establishment has been achieved through Ecuadorian regulations and the express consent of those who protect the land and its species. perennially and consciously; considering in a special way the processes that have been carried out in different scenarios of the indigenous peoples and nationalities in which the application of this principle has been obscured, due to the non-existence of a concrete, precise and suitable procedure on the part of legal regulations, which means that this informalism and legal imprecision is an impediment to achieving an adequate Prior, Free and Informed Consultation. For this purpose, the pertinent and relevant legal documentary information on this topic was collected, which allowed it to be projected in this investigative process, in order to determine if in Ecuador, the aforementioned Prior Consultation process is applied effectively, and if not. If so, what are the main reasons that have not managed to combine the importance of this principle, with its proper application in this country, as provided for in the Constitution of the Republic of Ecuador.